Examining the Outcome of Osteosarcoma: 10-Year Experience in a Referral Center South of Iran - Gerami, Mohammad Hadi; Solooki, Saeed; Mansoori, Yaser; Moein, Seyed Arman; Jamali, Jamshid (Reports of Radiotherapy and Oncology, 2023)
Background: Osteosarcoma is a primary and malignant bone tumor. Currently, using neoadjuvant chemotherapy, surgery, and appropriate adjuvant chemotherapy, long-term survival of more than 70% can be expected for patients affected by this disease. Therefore, the combination of different treatment methods increases the chances of saving the limb. Objectives: In this study we intend to share our 10-year experience in the management of osteosarcoma in Shiraz as the referral center of south of Iran. Methods: In this retrospective cohort study, 56 patients with osteosarcoma who were referred to Chamran and Namazi hospitals between 2008 and 2017, were included. Age, sex, site of involvement, presence of metastasis, treatment procedure, treatment outcomes, and survival time were studied. Kaplan-Meier method was used for survival analysis. Log rank test was applied for comparison of survival time according to sex. SPSS software version 25 (SPSS Inc., Chicago, US) was used for statistical analysis. Significance level considered P-value less than 0.05. Results: Among these patients, 33 were men 23 were women, with an average of 10 to 68 years old. In our study, distal femur was the most common site for osteosarcoma. Moreover, 44.6% of the patients undergone amputation. The best treatment results are in patients who received neoadjuvant chemotherapy followed by surgery. Finally, 77% of patients had a 2-year survival rate, and 57% had a 5-year survival rate. Conclusions: There has been a significant advancement in the treatment of osteosarcoma. A multifaceted approach to this disease, including surgery and chemotherapy has increased the possibility of better prognosis for this disease. Early diagnosis and appropriate treatment in the form of neoadjuvant chemotherapy, surgery with appropriate margin removal, and adjuvant chemotherapy are suggested for this tumor.